PANDANGAN FEMINISME DALAM LAGU DEAR FUTURE HUSBAND OLEH MEGHAN TRAINOR - Rifdah Ayu Fajri; Angkita Wasito Kirana (ETNOLINGUAL, 2020)
AbstractThis paper aims to examine the application of the concept of feminism at the level of the American family through the analysis of a song entitled Dear Future Husband, sung by Meghan Trainor, an American singer. In analyzing this phenomenon the author uses the concept of feminism which is promoted by Kate Millett (1970) and mimetic approach. From the results of this study, it is found that in this song, the concept of feminism is still not fully applied in the family sphere. This is because women, as the subject of feminist understanding, still do not fully want this concept for themselves. Keywords: feminism, family, Meghan Traynor, America AbstrakMakalah ini bertujuan untuk mengkaji aplikasi konsep feminisme dalam tataran keluarga Amerika melalui analisa diskursi lagu berjudul Dear Future Husband yang dinyanyikan oleh Meghan Trainor, seorang penyanyi berkebangsaan Amerika. Dalam menganalisa fenomena ini penulis menggunakan konsep feminisme yang diusung oleh Kate Millett (1970) dan pendekatan mimetik. Dari hasil penelitian ini, didapat bahwa pada pada lagu ini, konsep feminisme masih belum sepenuhnya diaplikasikan dalam lingkup keluarga. Hal ini dikarenakan perempuan, sebagai subyek dari paham feminis masih belum sepenuhnya menginginkan konsep tersebut bagi dirinya sendiri. Kata kunci : feminisme, keluarga, , Meghan Traynor, Amerika